Assessment Of Challenges And Opportunities Of Open Source Software Policies In Malaysia Companies - Nathan, Yogeswaran (2004)
This research paper investigate the level of Open Source Software adoption and implementation by Malaysia ICT (Information Communication Technology) companies by examining the result of a survey conducted among ICT companies with MSC status. This research also discusses the cause of those problems, opportunities and the possible solutions to encourage the usage of Open Source Software in Malaysia.